Human resources for health and burden of disease: an econometric approach - Castillo-Laborde Carla (BMC, 2011)
Abstract Background The effect of health workers on health has been proven to be important for various health outcomes (e.g. mortality, coverage of immunisation or skilled birth attendants). The study aim of this paper is to assess the relationship between health workers and disability-adjusted life years (DALYs), which represents a much broader concept of health outcome, including not only mortality but also morbidity. Methods Cross-country multiple regression analyses were undertaken, with DALYs and DALYs disaggregated according to the three different groups of diseases as the dependent variable. Aggregate health workers and disaggregate physicians, nurses, and midwives were included as independent variables, as well as a variable accounting for the skill mix of professionals. The analysis also considers controlling for the effects of income, income distribution, percentage of rural population with access to improved water source, and health expenditure. Results This study presents evidence of a statistically negative relationship between the density of health workers (especially physicians) and the DALYs. An increase of one unit in the density of health workers per 1000 will decrease, on average, the total burden of disease between 1% and 3%. However, in line with previous findings in the literature, the density of nurses and midwives could not be said to be statistically associated to DALYs. Conclusions If countries increase their health worker density, they will be able to reduce significantly their burden of disease, especially the burden associated to communicable diseases. This study represents supporting evidence of the importance of health workers for health.